NEGOTIATING POLITENESS ACROSS CULTURES: A DISCOURSE ANALYSIS OF EXPLICITNESS AND DIRECTNESS IN TRANSLATING HAPPINESS SENTENCES - Silalahi, Onasis (ppjbsip, 2026)
This study examines the discourse strategies of explicitness and directness in translating The Subtle Art of Not Giving a Fck* from English (a low-context culture) into Indonesian (a high-context culture). Focusing on 35 “happiness-related” sentences, the research applies contrastive analysis framed by Hall’s high/low context cultural theory and Murtisari’s explicitation/implicitation typology. The analysis reveals that while Indonesian translations largely preserve the explicit and direct style of the English original, they frequently employ scalar explicitation by adding lexical items for clarification and categorical explicitation by adjusting for politeness and formality. These shifts reflect the high-context cultural preference for respectful and relational communication, often realized through lexical additions, passive constructions, and polite address forms such as Anda. However, some translations result in semantic deviations, where terms like happiness are rendered as kegembiraan (joy) rather than kebahagiaan (long-term happiness), subtly altering the meaning of the discourse. From a discourse perspective, these shifts demonstrate how translation negotiates cultural expectations, balancing the author’s direct style with the target culture’s politeness norms. The study argues that such micro-level changes have macro-level implications for understanding translation as a discourse practice: not merely transferring meaning but recontextualizing values, identity, and communicative style. While limited in scope to one text and theme, the findings underscore the importance of integrating discourse analysis into translation studies to uncover cultural ideologies embedded in language. Future research should extend to diverse genres and cultural contexts to further explore how translation mediates discourse across societies.